The Influence of Benevolent Funds and Zakat Funds on The Reputation of Bank Syariah Indonesia for The 2018-2022 Period - Wewis Gilang Sari; Awaluddin Awaluddin; Loso Judijanto; Iiz Izmuddin; Al-Amin; Hadi Subeno; Fahmi Sulaiman (Universitas 17 Agustus 1945 Semarang, 2024)
Reputation has the potential to influence a company's performance, the support it receives from the public, and the bank's ability to obtain the necessary funding. This research aims to evaluate the impact of benevolent funds and zakat funds on the reputation of Indonesian sharia banks (BSI) in the 2018-2022 period. The research uses quantitative methods with the aim of understanding the relationship between construction variables which include several variables and other variables, to predict variable X1 (benevolent funds), variable X2 (zakat funds), and variable Y (reputation) on BSI. The data used is document data, especially annual reports published by BSI every quarter on the Indonesia Stock Exchange (BEI) in the 2018-2022 period and collected via the official BSI website. The research results show that, partially, the path coefficient for the use of benevolent funds (PDK) has a positive value of 0.18 with a p-value of 0.18. This means that the use of benevolent funds has a positive effect on reputation with a contribution of 18%. Meanwhile, the use of zakat funds (PDZ) on reputation has a positive path coefficient of 0.53 with a p-value of 0.1 which is smaller than 0.05. This shows a positive relationship between the use of zakat funds and reputation, with a contribution of 49%. In the indirect and total effects table, the use of zakat funds shows a positive and significant relationship to reputation with a contribution of 53%. Both the use of benevolent funds and zakat funds have a positive impact on reputation, with a p-value of 0.002 which is smaller than 0.05. In addition, the R-squared for the reputation variable is 0.487, indicating that the contribution of the PDK (X1) and PDZ (X2) variables to reputation (Y) is 48.7%, and the remaining 51.3% is influenced by other variables outside the model study.